Mirror, mirror by the stairs: the impact of self-awareness on stair versus elevator use in college students - Hodgin, Katie L., author; Graham, Daniel, advisor; Nelson, Tracy, committee member; Witt, Jessica, committee member (Colorado State University. Libraries, 2015)
Previous research has indicated that self-awareness-inducing mirrors can successfully incite behavior change, such as encouraging helping. However, few studies have examined how mirror exposure and perceived body size influence physical activity participation. The present study assessed stair versus elevator use on a western college campus and hypothesized that mirror exposure would increase stair use. One hundred and sixty-seven students enrolled in an introductory psychology course were recruited to take a survey interested in their "transportation choices" at an indoor campus parking garage. Participants were individually exposed to either no mirror, a standard full-length mirror, or a full-length mirror manipulated to make the reflected body size appear either slightly thinner or slightly wider than normal before being asked to go to the fourth floor of the garage for a survey. Participants’ choice of floor climbing method (stairs or elevator) was recorded and they were administered an internet-based survey assessing demographic information, body mass index (BMI), self-awareness, and other variables likely to be associated with stair use. Results from logistic regression analyses revealed that participants who were not exposed to a mirror (OR = 0.37, 95% CI: 0.14 – 0.96), males (OR = 0.33, 95% CI: 0.13 – 0.85), those with lower BMI (OR = 0.84, 95% CI: 0.71 – 0.99), those with higher exercise participation (OR = 1.09, 95% CI: 1.02 – 1.18), and those engaging in more unhealthy weight-control behaviors (OR = 1.55, 95% CI: 1.14 – 2.11) were significantly more likely to take the stairs. Implications and future directions are discussed.
Keywords: self-awareness; mirror; stair use